Response surface modelling and optimization of temperature and holding time on dual phase steel. (2021) - Olorundaisi, Emmanuel; Jamiru, Tamba; Adegbola, Taoreed Adesola
Abstract: Low carbon steel of composition 0.98 wt% quenched in water, was subjected to heat treatment at different holding times, to improve on the mechanical properties of Dual Phase (DP) steel. This study investigates the influence of operating parameters on the mechanical properties of DP steels, using response surface methodology (RSM) to develop a prediction model. To reduce the number of experiments and eliminate trial by error approach, design of experiment (DOE) approach was adopted. In developing the model, temperature and holding time were considered as the model variables. The optimum operating parameters were predicted using the user-defined design (UDD) under RSM and the result was validated through experiments. Improved mechanical properties with increasing temperature and holding time were observed. At a holding time of 30 min and 650 °C, DP steel quenched in water compared with a holding time of 60 min at a temperature of 800 °C, shows a Hardness value of 143.26 HV as against 168.82 HV, Ultimate tensile strength of 500.641 MPa as against 598.317 MPa, and Yield strength of 257.333 MPa as against 303.246 MPa. These findings show that at a longer holding time and higher temperature, low carbon steel can be exploited for the production of Dual Phases steel.